Fall of the 'platonic guardians' - Liberalism, criminology and political responses to crime in England and Wales - Loader, I (2006)
This paper offers a critical reconstruction and reinterpretation of the disposition towards the governance of crime that was ascendant in England and Wales during the middle decades of the twentieth century - namely, liberal elitism, or what I term 'Platonic guardianship'. Drawing upon documentary sources, and extended oral history/biographical interviews with retired Home Office officials, penal reformers and criminologists, I examine the express and implied values and beliefs that constitute this take on political responsibility towards crime and the public passions it arouses, and consider the senses in which it may be plausibly described, ideologically, as liberal. I then explore three 'moments' of contention during which the legitimacy of liberal elitism was called into question over the last several decades - the 'nothing works' assault on rehabilitation in the 1970s, the rise of 'law and order' politics in the 1980s, and the populist and punitive turn taken by penal politics since 1993. In each case, I outline briefly the nature of the charges levelled at the commitments and practices of Platonic guardianship and assess - drawing upon the interview material - the perceived scale and effects of each challenge. I conclude by reflecting on the sociological preconditions and normative limitations of Platonic guardianship as a mode of rule, and on what we may draw from it today in our efforts to make sense of, and transcend, the febrile contemporary politics of crime.